75 Years Smart Library Research on Scopus Database: A Bibliometric Analysis and Information Mapping - Arwanto, Arwanto; Wigati, Dewi Endah (Indonesian Journal of Librarianship, 2024)
Abstract Background: Library employs advanced technology to facilitate digital access and offer smart services. Despite numerous benefits, different issues arise with the implementation of smart library, such as limited accessibility and technological challenges. Purpose: This research aimed to analyze the mapping trends and accessibility challenges in smart library implementation. Method: A quantitative paradigm was used with a bibliometric method and the results were collected, summarized, and analyzed using the keyword from the Scopus database, focusing on titles without restricting the publication year. In addition, data were analyzed and mapped using VOSviewer. Result: The information that describes the research findings. A total of 347 articles were found in the Scopus database and 260 were identified after analyzing for high relevance. Meanwhile, the number of publications increased significantly in 2018, with continued growth through 2021 and 2022. The peak research activity occurred in 2021 and 2022, with 61 and 58 publications, respectively. Conclusion: The most frequently occurring keywords included book, internet, Internet of Things (IoT), university library, library service, transformation, academic library, RFID, smart service, and public library. In this context, research in the field was related to information technology, services, and transformation into smarter and more efficient library.